A systematic review of the prevalence and types of obstetric violence on the health and well-being of women in Brazil (Research, Society and Development, 2023)
Obstetric violence is an alarming issue that affects countless women during pregnancy and childbirth, constituting a type of gender violence that generates significant negative consequences on women's physical and mental health. Furthermore, it can lead to serious complications both during and after childbirth, negatively impacting the woman's self-esteem and confidence in relation to the entire gestational process. With the aim of raising the main types of obstetric violence in Brazil, this work proposed to carry out a systematic review based on searches in the Pubmed and Scopus databases, using the terms "Obstetric violence", "Brazil", "obstetric care". " and their combinations. The analysis of 12 articles allowed the identification of a worrying situation: obstetric violence is a generalized and disseminated problem in the country. The most common types of violence include unnecessary medical interventions, mistreatment, disrespect for women's autonomy during childbirth, inhumane treatment and neglect. In this sense, it is essential to adopt measures to prevent and combat obstetric violence, such as making society aware of women's rights during pregnancy and childbirth, promoting adequate training of health professionals and implementing public policies to protect the health and women's well-being.